Peran Guru dalam Suksesnya Implementasi Kebijakan Pendidikan Inklusif di Sekolah Dasar - Sari, Ratna Tiara; Yani, Dwi; Adawiyah, Siti; Ayu Oktaviani, Salsabila; Nur Isnaini, Putri; Prihantini, Prihantini (Lembaga Intelektual Muda (LIM) Maluku, 2023)
This study explores the role of teachers in the context of successful implementation of inclusive education policies in primary schools. Using a descriptive method with Literature Review technique to present a complete and up-to-date picture of empirical studies published in the last 15 years that identify factors that influence the role of teachers and their impact on the effectiveness of inclusion policies. The results highlight that teachers' deep understanding of student diversity, implementation of inclusive learning strategies, and active collaboration with peers and parents play an important role in achieving policy goals. Teachers' roles are not only limited to academic learning, but also involve fostering positive social relationships in the classroom. In addition, there is a need for additional training in inclusion and an understanding of students' special needs. Continuous evaluation of teachers' roles in implementing this policy is key to continuous improvement